Aisyiyah dan Kiprahnya dalam Pembinaan Keluarga Sakinah - Adawiah, Rabiatul (Jurnal Muadalah, 2013)
Forming a happy family is not as easy as turning the palm of the hand , but a struggle that requires sacrifice and awareness is high enough. Women have an important position in the family life and was instrumental in creating a happy family. This study tried to describe about the pursuit of womens organizations that Sakinah Family Aisyiyah in coaching in South Kalimantan. The formulation of the problem studied is how the concept of harmonious family by Aisyiyah South Kalimantan , and how the pursuit of womens organizations in fostering harmonious family. The result showed that the concept of family Aisyiyah known as the